PEMBERDAYAAN PEREMPUAN DALAM MENINGKATKAN KEMANDIRIAN USAHA MELALUI PELATIHAN KETRAMPILAN MENYULAM PADA USAHA PENINGKATAN PENDAPATAN KELUARGA SEJAHTERA (UPPKS) SUMBER REZEKI KELURAHAN TANGKERANG LABUAI - Roza Linda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
This research aims to determine, describe and analyze the empowerment of women in enhancing self-reliance through skills training effort embroider on UPPKS Sumber Rezeki. The method used in this research is a qualitative method. Technique of determining the informant by using judgement sampling. The collection of data by means of observation, interviews and documentation and validation of the data used in this research is triangulation sources and triangulation of data. Results from this research was conducted UPPKS Sumber Rezeki is empowerment of women in developing the potential and expected embroidering skills training can be a capital in enhancing the independence of the business. Based on the five approach to the process of empowerment of women through skills training embroider on UPPKS Sumber Rezeki already said to be very good for strengthening approach, protection and support for the approach while possibility and maintenance aspects need to be improved better.